Effectiveness of online self-help for suicidal thoughts: results of a randomised controlled trial. - Bregje A J van Spijker; Annemieke van Straten; Ad J F M Kerkhof (PLoS ONE)
Background Many people with suicidal thoughts do not receive treatment. The Internet can be used to reach more people in need of support. Objective To test the effectiveness of unguided online self-help to reduce suicidal thoughts. Method 236 adults with mild to moderate suicidal thoughts were randomised to the intervention (n=116) or a waitlist control group (n=120). Assessments took place at baseline, and 2, 4 and 6 weeks later. Primary outcome was suicidal thoughts. Secondary outcomes were depressive symptoms, anxiety, hopelessness, worry, and health status. Results The intervention group showed a small significant effect in reducing suicidal thoughts (d=0.28). Effects were more pronounced for those with a history of repeated suicide attempts. There was also a significant reduction in worry (d=0.33). All other secondary outcomes showed small but non-significant improvements. Conclusions Although effect sizes were small, the reach of the internet could enable this intervention to help many people reduce their suicidal thoughts. Trial registration Netherlands Trial Register NTR1689.